The secondary discharge supported by microdischarge in vortex flow - Solomenko, Ok.V.; Lendiel, V.V.; Chernyak, V.Ya.; Kalustova, D.O.; Iukhymenko, V.V.; Martysh, E.V.; Prysiazhnevych, I.V.; Shapoval, V.O. (Вопросы атомной науки и техники, 2014)
This research studies the DC microdischarges properties in the air vortex flow. The electrical parameters of the discharge and optical characteristics of the microdischarge plasma jet have been studied. The electronic excitation temperatures has been determined by Boltzmann plots using oxygen atom multiplets (777, 844, 926 nm). Also, there are the molecular bands of NO, OH, and N₂ (B-A) and N₂ (C-B) in the microdischarge plasma spectrum. The vibrational and rotational excitation temperatures have been determined.